2007
DOI: 10.1097/spc.0b013e3281108014
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage to the gastrointestinal tract: mechanisms, diagnosis, and management

Abstract: The risk of injury to the intestine is dose limiting during abdominal and pelvic radiation therapy. Delayed bowel toxicity is difficult to manage and adversely impacts the quality of life of cancer survivors. More than 200,000 patients per year receive abdominal or pelvic radiation therapy, and the estimated number of cancer survivors with postradiation intestinal dysfunction is 1.5-2 million. Worthwhile progress towards reducing toxicity of radiation therapy has been made by dose-sculpting treatment technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(78 citation statements)
references
References 68 publications
0
75
0
3
Order By: Relevance
“…The damage caused by radiation on gastrointestinal mucosal barrier is the most important dose limiting factor in abdominopelvic radiotherapy for cancer treatment 9,16 . This clinical tableu may appear with severe symptoms such as diarrhea, tenesmus and rectal bleeding 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The damage caused by radiation on gastrointestinal mucosal barrier is the most important dose limiting factor in abdominopelvic radiotherapy for cancer treatment 9,16 . This clinical tableu may appear with severe symptoms such as diarrhea, tenesmus and rectal bleeding 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent literature showed that, a significantly increase in the bacterial overgrowth and translocation by destroying the intestinal mucosal barrier and affecting intestinal peristaltic movement is seen in the abdominal region affected by radiation 4,8 . This complication can be seen approximately in 10-15% of the patients after abdominal radiation theraphy and is the most important limiting factor for the radiotherapy dose in the abdominopelvic region 9 .…”
Section: Radiation Was First Described By Willhelm Conradmentioning
confidence: 99%
“…The GI tract is among the most radiosensitive organ systems in the body owing to the high rate of turnover of mucosal and intestinal cells. In addition to the intestinal epithelium crypt, radiation exposure damages supporting structures such as endocrine glands of the GI tract (14). The GI tract has been considered the largest endocrine organ because of its complement of endocrine cells, which produce a variety of peptides that are involved in GI motility, secretion, absorption, growth and development (15).…”
Section: Ars and The Gastrointestinal Tractmentioning
confidence: 99%
“…The gastrointestinal (GI) tract is one of the most radiosensitive organs in the body. Radiation exposure damages the intestinal crypts and endocrine glands of the GI tract (Hauer-Jensen, Wang, Boerma, Fu, & Denham, 2007). Early radiation enteropathy occurs during radiotherapy as a result of intestinal crypts cell death, lacking the villus epithelium replacement and mucosal inflammation processes (Hauer-Jensen, Denham, & Andreyev, 2014).…”
Section: Introductionmentioning
confidence: 99%